Loan Loss Provisions Hypotheses Tests for Banks in the United States - Yue, Zhennan (2019)
This paper adopts data of 75 United States commercial banks from 2011 to 2018 to test several hypotheses of loan loss provision named income smoothing, capital management, business cycle and bank efficiency hypothesis. Models such as pooled OLS, fixed effects (FE) model, random effects (RE) model, Stochastic Frontier Analysis (SFA) and Generalized Method of Moments (GMM) are employed for investigating the relation between selected independent variables and dependent variable loan loss provision to total assets for proving above hypotheses. From the final result, the evidences to support income smoothing and business cycle could be found, banks size and operating efficiency can also influence bank loan loss provision.